LEGAL REFORMS: PAST, PRESENT AND FUTURE Review of the section of the Faculty of Law of the North-West Institute of Management of the RANEPA, held within the framework of the VI International Nevsky Forum (St. Petersburg, June 25, 2022) - N. V. Razuvaev; N. K. Shmarko (Теоретическая и прикладная юриспруденция)
The article is a review of the speeches of the participants of the section of the Faculty of Law of the Northwestern Institute of Management of the RANEPA, held within the framework of the VI International Nevsky Forum (St. Petersburg, June 25, 2022) “Legal reforms: past, present and future”, which discussed the problems of reforms in the ﬁeld of law, as general problems of reforms in in the form of the need to deﬁne a clear goal and guidelines for reform, and in terms of reforms in certain legal areas (education, digitalization, legal history, constitutional law, civil law). In general, the participants agreed on the need to take into account the social, economic and political context when carrying out reforms and evaluating their results, clearly setting the goal of reforms, and the need to maintain, within the framework of current changes, adherence to unshakable ideas and principles of law, and constitutional law in particular.